Sperm competition dynamics: ejaculate fertilising efficiency changes differentially with time. - Pizzari, T; Worley, K; Burke, T; Froman, D (2008)
BACKGROUND: A fundamental challenge in evolutionary biology is to resolve the mechanisms that maintain paternity a hypervariable fitness component. Because females are often sexually promiscuous, this challenge hinges on establishing the mechanisms through which the ejaculates of different males compete for fertilisation (sperm competition). The competitive quality of an ejaculate is mediated by the relative number of live sperm and their motile performance. The differential rate at which rival ejaculates lose their fertilising efficiency over time is therefore expected to influence the outcome of sperm competition. RESULTS: Here, we artificially inseminated into sets of replicate domestic hens, Gallus gallus domesticus, experimentally engineered heterospermic ejaculates containing a large number of low-quality sperm from one male, and a lower number of high-quality sperm from another male. Large, low-quality ejaculates fertilised the first eggs produced after insemination, but small, high-quality ejaculates prevailed in the long run despite their numerical disadvantage. CONCLUSION: Together, these results provide the first experimental demonstration that the relative competitive value of an ejaculate changes drastically over the time during which competing ejaculates are stored within the reproductive tract of a female, resulting in a marked temporal pattern of variation in paternity. A high level of replication makes these results robust. However, our study was restricted to few males of a well characterised study population, and future work should explore the generality of these results.